Normal Speed and Accuracy of Saccade and Vergence Eye Movements in Dyslexic Reader Children. (19th January 2010) - Bucci, Maria Pia; Vernet, Marine; Gerard, Christophe-Loïc; Kapoula, Zoï
Abstract : Objective . Latency of eye movements depends on cortical structures while speed of execution and accuracy depends mostly on subcortical brainstem structures. Prior studies reported in dyslexic reader children abnormalities of latencies of saccades (isolated and combined with vergence); such abnormalities were attributed to deficits of fixation control and of visual attention. In this study we examine speed and accuracy characteristics of horizontal eye movements in natural space (saccades, vergence and combined movements) in dyslexic reader children. Methods . Two paradigms are tested: gap paradigm (fixation offset 200 ms prior to target onset), producing shorter latencies, in both non-dyslexic reader and dyslexic reader children and simultaneous paradigm. Seventeen dyslexic reader children (mean age:12 ± 0.08 years) and thirteen non-dyslexic reader children (mean age:12 ± 1 years) were tested. Horizontal eye movements from both eyes were recorded simultaneously by a photoelectric device (Oculometer, Dr. Bouis). Results . For all movements tested (saccades, vergence, isolated or combined) and for both paradigms, the mean velocity and accuracy were similar in dyslexic readers and non-dyslexic readers; no significant difference was found. Conclusion . This negative but important result, suggests no dysfunction of brainstem ocular motor circuits in dyslexic readers. It contrasts results on latencies related to visual attention dysfunction at cortical level.